Single-Carbon-Nanotube Manipulations and Devices Based on Macroscale Anthracene Flakes - Shen, Boyuan (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.